2017
DOI: 10.2903/j.efsa.2017.4884
|View full text |Cite
|
Sign up to set email alerts
|

Update of the list of QPS‐recommended biological agents intentionally added to food or feed as notified to EFSA 6: suitability of taxonomic units notified to EFSA until March 2017

Abstract: The qualified presumption of safety (QPS) concept was developed to provide a harmonised generic pre‐evaluation to support safety risk assessments of biological agents performed by EFSA's scientific Panels. The identity, body of knowledge, safety concerns and antimicrobial resistance of valid taxonomic units were assessed. Safety concerns identified for a taxonomic unit are, where possible and reasonable in number, reflected as ‘qualifications’ which should be assessed at the strain level by the EFSA's scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…In contrast to QPS, the GRAS designation encompasses the substance/microbial culture and its specific application or usage (for example, in a particular type of product), rather than applying solely to the microorganism itself; thus, while for QPS the evaluation is at the level of the taxonomic unit (species), and applies to that unit independent of application, GRAS designation can be at the species or strain level because the specific application (including formulation, dosages, etc.) is considered (Ricci et al., ).…”
Section: Regulatory Aspects On the Use Of Aab As Food Culturesmentioning
confidence: 99%
“…In contrast to QPS, the GRAS designation encompasses the substance/microbial culture and its specific application or usage (for example, in a particular type of product), rather than applying solely to the microorganism itself; thus, while for QPS the evaluation is at the level of the taxonomic unit (species), and applies to that unit independent of application, GRAS designation can be at the species or strain level because the specific application (including formulation, dosages, etc.) is considered (Ricci et al., ).…”
Section: Regulatory Aspects On the Use Of Aab As Food Culturesmentioning
confidence: 99%
“…No safety concerns or reports on antimicrobial resistance have been described for the species H. denitrificans according to a recent assessment done by the EFSA BIOHAZ Panel. However, it has been concluded that the body of knowledge is limited and, therefore, this bacterial species cannot be taken into consideration for being included in the Qualified Presumption of Safety (QPS) list (EFSA BIOHAZ Panel et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Different strains of L. plantarum have emerged as functional LAB exhibiting a long history of safe use. It is considered as "generally recognized as safe" (GRAS) and has qualified presumption of safety (Ray and Joshi, 2014;Ricci et al, 2017). The versatility of L. plantarum makes it a good functional organism to be used in a wide range of applications in the food industry, especially as a starter culture.…”
Section: Introductionmentioning
confidence: 99%